Application of Renewable Solar Energy for Thermal Treatment of Milk: A Review - Chitranayak,; Sharanabasava,; P., Abhinash; Nagaratna,; Minz, P. S.; John, Hima; Priyanka,; Nagajjanavar, Kiran; Simha, Vikram (International Journal of Bio-resource and Stress Management, 2022)
In India the milk is consumed both in the raw (un-processed) as well as processed forms with the raw milk being consumed locally. The use of processed milk is prevalent through both the organized as well as un-organized sectors. The milk processing in the organized sector (20% of the total milk processed) is undertaken to produce the pasteurized liquid milk as well as other value-added products. Solar energy is a cheap, omnipresent, and indigenous source of energy that produces a clean, pollution-free climate. In recent years, the use of solar energy has risen to new heights. Its driving force is the ongoing quest for an alternative power source due to the perceived shortage of fossil fuels. As the price of fossil fuels continues to increase, it has become much more common. The planet absorbs more energy from the sun in a single hour than the entire world consumes in a year. Its use has proved to be the most cost-effective, as most systems in individual applications only need a few kilowatts of electricity. Solar collectors transform solar energy into thermal energy for heating applications, which is the easiest and most effective way to do it. The dairy industry is one of the industries where thermal processing is a crucial unit activity. Solar energy can thus be used to heat water, sterilize cans and bottles, and pasteurize milk. This paper examines the use of solar energy in the pasteurization of milk.